1990
DOI: 10.1172/jci114647
|View full text |Cite
|
Sign up to set email alerts
|

A conserved idiotype and antibodies to retroviral proteins in systemic lupus erythematosus.

Abstract: 22 of 61 systemic lupus erythematosus (SLE) patients produced antibodies to the p24 gag protein of HIV-1 demonstrated by Western blotting. 20 of these 22 patients (91%) also express the 4B4 idiotype (Id 4B4) previously identified on a human anti-Sm monoclonal antibody called 4B4. This represents an enrichment for this Id (seen in only 52% of SLE patients generally). Eight of these 22 SLE patients also have anti-Sm antibody activity. Sm partially inhibits the antibody binding of p24 gag suggesting immunologic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(63 citation statements)
references
References 13 publications
1
60
2
Order By: Relevance
“…Separate studies had established correlation of WBi results with systemic lupus erythematosus, rheumatoid factor, leprosy, post-measles virus infection, elevated bilirubin, polyclonal gammopathies, and hemodialysis (88,89,90,98). However, a study by Urnovitz et al (96) showed that, in addition to autoimmune diseases, malignancies, urologic disorders, sexually transmitted diseases, and multiple blood transfusions could also be responsible for the occurrence of WBi results.…”
Section: Causes and Frequency Of Wbi Resultsmentioning
confidence: 99%
“…Separate studies had established correlation of WBi results with systemic lupus erythematosus, rheumatoid factor, leprosy, post-measles virus infection, elevated bilirubin, polyclonal gammopathies, and hemodialysis (88,89,90,98). However, a study by Urnovitz et al (96) showed that, in addition to autoimmune diseases, malignancies, urologic disorders, sexually transmitted diseases, and multiple blood transfusions could also be responsible for the occurrence of WBi results.…”
Section: Causes and Frequency Of Wbi Resultsmentioning
confidence: 99%
“…In our case, by contrast, cross-reaction with HIV was detected using a particle agglutination assay; Western blotting showed no such cross-reaction. In one study, antibodies reactive with HIV p24 were detected in 22 of 66 patients with SLE (8). The investigators speculated that the mechanism of the reactivity with HIV p24 was antigenic mimicry between self-epitopes, such as small ribonucleoproteins (so-called Sm) or retroviral antigens.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course is aggressive, with a median survival of less than three years, largely owing to associated immune dysregulation with opportunistic infection (2). The characteristic clinical features of AITL are widely believed to be related to an abnormal pattern of cytokine expression by neoplastic T cells and various non-neoplastic cells (7,8). Although AITL accompanies autoimmune disease or hypergammaglobulinemia, there are a few reports on the complication of false-positive HIV antibody test in AITL.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies reactive with HIV or HTLV Gag (CA, p24) are common in patients with autoimmune diseases such as MS, SS, and SLE (369,407,477,478). In general, anti-Env antibodies are not present in these individuals, although sera from patients with mixed connective tissue disease are reported to contain neutralizing antibodies that block HIV infection (127).…”
Section: Detection Of Serum Antibodies To Retrovirusesmentioning
confidence: 99%